Bibliometrics analysis and the role of nanocatalysts in wastewater remediation - J. Aravind; M. Kamaraj; P. Suresh Babu (Global Journal of Environmental Science and Management)
To address global concerns such as population expansion, urbanization, and industrialization, which are contributing to increased water pollution and shortages, sustainable water management relies on wastewater reuse. The purpose of this review is to investigate the significant role that hybrid catalytic materials and nanocatalysts play in the process of improving wastewater treatment technologies. By employing these materials and other advanced oxidation techniques, nanocatalysts are evaluated to assess their effectiveness in eliminating heavy metals and degrading persistent organic contaminants. The bibliometric assessment of research trends from 2015 to 2024 reveals a growing emphasis on the applications of nanotechnology in wastewater treatment. Within the scope of this review, the internal and extrinsic parameters that influence catalytic performance are investigated. These factors include particle size, light intensity, catalyst loading, and ambient pH conditions. Nanocatalysts hold great promise; however, several lingering concerns need to be addressed. These issues include high synthesis costs, scalability challenges, and environmental toxicity. These issues underscore the need to develop sustainable synthesis procedures, improved recovery mechanisms, and policy frameworks. Recent achievements in this sector include synthesizing nanomaterials that are safe for the environment, developing hybrid catalytic systems, and integrating these systems into existing treatment infrastructures to enhance efficiency and cost-effectiveness. The resolution of these issues will contribute to the establishment of nanocatalysts as transformative tools and green materials for wastewater treatment, for promoting the sustainability of water on a global scale and protecting the environment. The application of these hybrid materials for wastewater treatment is a topic of significant interest in environmental research.